Managerial incentives: on the Near Linearity of Optimal Compensation - Diamond, Peter (Journal of Political Economy, 1998)
Contracts are examined when outcomes depend on managers' choices as well as efforts. As the cost of effort shrinks relative to payoffs, the optimal contract converges to a linear payoff if the control space of the agent has full dimensionality, but not otherwise. Thus, when the agent can trade expected return for greater correlation with other returns, it is better to ignore relative performance when the cost of effort is small. When the choices include all fair gambles and hedges, the linear schedule is no more expensive than any other schedule that induces effort. Unfair gambles are examined as well.